Perawatan Luka pada Pasien Ulkus Diabetik Grade 3 dengan Hydrogel di Puskesmas Kelarik; Studi Kasus - Diah Ratri Larasati; Haryanto, Haryanto (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Introduction; Grade 3 diabetic ulcers are chronic wounds that require special care to achieve optimal healing. Hydrogel, as a modern dressing, plays a critical role in maintaining wound moisture and accelerating the healing process. This study aims to assess the effectiveness of hydrogel in managing grade 3 diabetic ulcers at primary health care. Methods; A case study was conducted involving one patient, Mr. S, who presented with impaired tissue integrity. The nursing intervention included wound care using hydrogel dressings, focusing on maintaining wound moisture while managing skin tissue through autolytic and mechanical debridement. The treatment was administered routinely for three days at Kelarik Primary Health Care. Wound progress was evaluated using the Bates-Jensen Wound Assessment Tool. ResultsSignificant wound improvement was observed, demonstrated by a reduction in necrotic tissue and an increase in granulation and epithelialization tissue. Hydrogel effectively maintained wound moisture and enhanced patient comfort during the care period. DiscussionThe application of hydrogel dressings facilitated a rapid healing response by optimizing the wound environment, consistent with existing literature. This care approach is suitable to be implemented as an effective wound management method in primary healthcare. Conclusion; Hydrogel wound care for grade 3 diabetic ulcers at primary health care proven to accelerate healing and improve patient comfort, supporting its use as a primary treatment choice for diabetic wounds.